2009
DOI: 10.1073/pnas.0908953107
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s-related endosome dysfunction in Down syndrome is Aβ-independent but requires APP and is reversed by BACE-1 inhibition

Abstract: An additional copy of the β-amyloid precursor protein (APP) gene causes early-onset Alzheimer’s disease (AD) in trisomy 21 (DS). Endosome dysfunction develops very early in DS and AD and has been implicated in the mechanism of neurodegeneration. Here, we show that morphological and functional endocytic abnormalities in fibroblasts from individuals with DS are reversed by lowering the expression of APP or β-APP-cleaving enzyme 1 (BACE-1) using short hairpin RNA constructs. By contrast, endosomal pathology can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
317
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(342 citation statements)
references
References 36 publications
19
317
0
Order By: Relevance
“…In the current study, we found that V 0 ATPase is both oxidized and polyubiquitinated (DS vs. Ctr Y and Ctr O vs. Ctr Y), and we hypothesize that these modifications decrease the V 0 -ATPase proton pump activity consistent with autophagy dysfunction. Accordingly, the Nixon group has demonstrated reduced acidification of lysosomes in AD (73), and genetic mutation of lysosomal ATPase is among the risk factors recognized to contribute to autophagy-related neurodegenerative diseases (37,52). Furthermore, disturbance of autophagosome formation coupled with hyperactivation of the mTOR pathway is observed in DS brain, before and after development of AD pathology (59).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that V 0 ATPase is both oxidized and polyubiquitinated (DS vs. Ctr Y and Ctr O vs. Ctr Y), and we hypothesize that these modifications decrease the V 0 -ATPase proton pump activity consistent with autophagy dysfunction. Accordingly, the Nixon group has demonstrated reduced acidification of lysosomes in AD (73), and genetic mutation of lysosomal ATPase is among the risk factors recognized to contribute to autophagy-related neurodegenerative diseases (37,52). Furthermore, disturbance of autophagosome formation coupled with hyperactivation of the mTOR pathway is observed in DS brain, before and after development of AD pathology (59).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an extra copy of APP is sufficient to cause endosomal enlargement and intracellular trafficking defects 141,142 via an Aβ-independent mechanism 143 . Enlargement of endosomes in trisomic neurons may cause axonal trafficking defects that contribute to neuronal degeneration 141 .…”
Section: Disruption Of Secretory and Endosomal Systemsmentioning
confidence: 99%
“…Conversely, βAPP expression is decreased in somas of neurons proximal to Aβ plaques in normal aging and in AD, and such βAPP seems to be redistributed from the neuron soma to dystrophic neurites (16), swollen stretches of axons, or dendrites containing mainly stalled vesicular traffic from the endocytic and autophagic pathways (17). These findings may be related to the accelerated endocytic activity and downstream dysfunction observed early on in DS and AD described in Jiang et al (1) in this issue of PNAS. The revelation that excess βAPP and its mediating factor βCTF, rather than Aβ, are the culprits in endocytic dysfunction in DS, together with the findings of other investigators regarding a role for overexpression of neuronal βAPP as a result of AD risk-conferring conditions, not only pinpoints βAPP-related targets for development of therapeutic interventions to prevent or forestall pathogenesis, but as importantly, it highlights the possibility that excess βAPP and its mediating factors such as βCTF and sAPP are more involved as initiators of pathogenesis than has previously been recognized.…”
Section: βApp Endosomes and Neurodegenerationmentioning
confidence: 70%
“…T he article by Jiang et al (1) in this issue of PNAS goes a good way toward explaining early consequences of elevated expression of β-amyloid precursor protein (βAPP) and its β-secretase-cleaved carboxyl-terminal fragment (βCTF) in the endocytic dysfunction present early on in Alzheimer's disease (AD) and Down's syndrome (DS or trisomy 21). The authors pose a straightforward question: is duplication of the βAPP gene in DS sufficient to precipitate endocytic dysfunction?…”
mentioning
confidence: 99%